Are Females Better Than Males In Communication In Second Language? - RUDZINSKA, IEVA (Journal of Education Culture and Society, 2020)
Although research in education, including worldwide Programme for International Stu-dent Assessment (PISA) by the Organisation for Economic Co-operation and Development (OECD) and Progress in International Reading Literacy Study (PIRLS) by the International Association for the Evaluation of Educational Achievement, shows that female language learners outdo their male counterparts in the development of verbal skills, a number of re-searchers have strongly challenged that claim. The aim of this paper is to find out whether professional foreign language competence in a higher education institution (HEI) in Latvia is different between females and males. In order to determine this, we have analyzed final grades and presentation scores (lecturer, peer and self-assessment) of students in an ESP (English for Specific Purposes, in our case: Sport English) course, as well as their levels of second language acquisition, obtained in centralized secondary school leaving exams, which serves as the basis for further development of professional foreign language competence in a sport related HEI. Whereas grades, scores and levels are considered in the present paper as depen-dent variables, gender constitutes an independent variable. A series of Mann-Whitney U tests has revealed no significant difference in male and female achievement in centralized school leaving exam in second language (English); in final grades, obtained by students in an ESP course; and in lecturer assessment of student presentations in the ESP course. However, the analysis of peer assessment of student presentations in the ESP course reveals that females tend to overestimate themselves and their peers. The latter observation, as this paper argues, may result from the fact that sport related HEI students are characterized by increased self-esteem (Rudzinska, 2007).